Reanalysis of Structures A Unified Approach for Linear, Nonlinear, Static and Dynamic Systems - Kirsch, Uri (Solid Mechanics and Its Applications, 2008)
This book deals with various computational procedures for multiple repeated analyses (reanalysis) of structures, and presents them in a unified approach. It meets the need for a general text covering the basic concepts and methods as well as recent developments in this area. Reanalysis is common to numerous analysis and design tasks such as nonlinear analysis, structural optimization, damage analysis, and probabilistic analysis. The book discusses various analysis models, including linear and nonlinear analysis, static and dynamic analysis, and design sensitivity analysis. It demonstrates how various concepts and methods are integrated to achieve effective solution procedures. The approach presented has several advantages in terms of generality, efficiency of the calculations, accuracy of the results and ease of implementation. Efficiency and accuracy considerations are discussed and illustrated. To clarify the presentation, many illustrative examples and numerical results are demonstrated. The text is related to a wide range of applications in such fields as Mechanical Engineering, Aerospace Engineering, Civil Engineering, and Naval Architecture. This should prove useful to students, researchers, analysts and consultants involved in analysis and design of structures. Previous books on structural analysis do not cover most of the material presented in the book.